2022
DOI: 10.1096/fj.202200212r
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofDrosophila NUS1results in cholesterol accumulation and Parkinson’s disease‐related neurodegeneration

Abstract: NgBR is the Nogo‐B receptor, encoded by NUS1 gene. As NgBR contains a C‐terminal domain that is similar to cis‐isoprenyltransferase (cis‐IPTase), NgBR was speculated to stabilize nascent Niemann‐Pick type C 2 (NPC2) to facilitate cholesterol transport out of lysosomes. Mutations in the NUS1 were known as risk factors for Parkinson's disease (PD). In our previous study, it was shown that knockdown of Drosophila NUS1 orthologous gene tango14 causes decreased climbing ability, loss of dopaminergic neurons, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Specifically, the loss of UCH deubiquitination promotes mitochondrial autophagy by activating the expression of AMPK and ULK1 (Ham et al, 2021). In Drosophila, researchers used CRISPR-Cas9 to knock out tango14, the homologous gene of NUS1, and found that the lifespan of Drosophila was shortened, and cholesterol accumulation appeared in dopaminergic neurons, which confirms that this gene is associated with the occurrence of PD due to lipid metabolism abnormalities (Xue et al, 2022).…”
Section: Construction Of Pd Models With Small Model Animalsmentioning
confidence: 88%
“…Specifically, the loss of UCH deubiquitination promotes mitochondrial autophagy by activating the expression of AMPK and ULK1 (Ham et al, 2021). In Drosophila, researchers used CRISPR-Cas9 to knock out tango14, the homologous gene of NUS1, and found that the lifespan of Drosophila was shortened, and cholesterol accumulation appeared in dopaminergic neurons, which confirms that this gene is associated with the occurrence of PD due to lipid metabolism abnormalities (Xue et al, 2022).…”
Section: Construction Of Pd Models With Small Model Animalsmentioning
confidence: 88%
“…Previous studies have suggested that dolichol plays a crucial role in membrane trafficking, particularly between the ER and lysosomal-endosomal system, which is critical for brain development ( Wu et al, 2017 ; Stojkovska et al, 2022 ). In addition, DHDDS can form a complex with the NUS1-encoded Nogo-B receptor (NgBR) ( Bar-El et al, 2020 ), another key gene involved in neurodegeneration ( Xue et al, 2022 ), which can further regulate protein glycosylation ( Edani et al, 2020 ). In this study, the recurrent pathogenic mutation (NM_001243564.1, c.113G>A/p.…”
Section: Discussionmentioning
confidence: 99%